The Effect of Environmental Uncertainty, Company Size, Strategic Changes on Financial Performance and Company Value with Good Corporate Governance as a Moderation Variable in Manufacturing Companies Listed on the Indonesia Stock Exchange - Firmansyah, Muhammad Nizar; Nugroho, Mulyanto; Rahmiyati, Nekky (International Journal of Economics (IJEC), 2025)
This study aims to analyze the influence of environmental uncertainty, company size, and strategic changes on financial performance and company value in manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) for the 2020-2022 period. With a quantitative approach using SEM-PLS, this study analyzed 111 data from 37 companies based on financial statements and annual reports. The results show that environmental uncertainty does not have a significant influence on financial performance or company value, either directly or through financial performance mediation. In contrast, the size of the company has a significant influence on the company’s financial performance and value, reflecting the stability and attractiveness of large companies in the eyes of investors. However, strategic changes do not have a significant effect on financial performance or company value, either directly or through financial performance as a mediator. In addition, the implementation of Good Corporate Governance (GCG) also does not mediate the relationship between financial performance and company value significantly. These findings underscore the importance of company size and financial performance as key determinants of company value in the stock market, while environmental uncertainty and strategic changes require further study to understand their impact.